2014
DOI: 10.1177/0954405414527268
|View full text |Cite
|
Sign up to set email alerts
|

Control rules of surface integrity and formation of metamorphic layer in high-speed milling of 7055 aluminum alloy

Abstract: Orthogonal experiments were conducted to investigate the effects of parameters on surface integrity in milling 7055 aluminum alloy. In order to correlate metamorphic layer with thermal and mechanical phenomena developed during milling, milling force and temperature fields of machined surface were obtained with finite element method, while milling speed and feed per tooth were paid particular attention to study formation of metamorphic layer. Experiment results show that when milling speed, feed per tooth, mill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
0
4
0
5
Order By: Relevance
“…Due to the coupling effect of various uncontrollable factors such as machine tools and cutting tools, there is a certain vibration interference on the uniformity of cutting speed distribution in the contact area of cutting tools and workpieces. 29,30 All the distractions would bring about the fluctuation of cutting forces in different periods during machining. Therefore, the final cutting force is the maximum value of cutting force in each direction, which is taken as the average value of 100 consecutive cutting force peaks or valleys, as shown in equations (2), (3), and (4).…”
Section: Resultsmentioning
confidence: 99%
“…Due to the coupling effect of various uncontrollable factors such as machine tools and cutting tools, there is a certain vibration interference on the uniformity of cutting speed distribution in the contact area of cutting tools and workpieces. 29,30 All the distractions would bring about the fluctuation of cutting forces in different periods during machining. Therefore, the final cutting force is the maximum value of cutting force in each direction, which is taken as the average value of 100 consecutive cutting force peaks or valleys, as shown in equations (2), (3), and (4).…”
Section: Resultsmentioning
confidence: 99%
“…To optimize machining parameters in end-milling 7055 alloy, orthogonal experiments were conducted to investigate the effects of parameters on surface integrity. 9 Meanwhile, many scholars found that SP-treated specimens made of precipitation hardened aluminum alloys showed better resistance to fatigue crack initiation by a factor of 1.2-6. [10][11][12] An analysis of surface integrity after SP is important to provide optimum fatigue properties.…”
Section: Introductionmentioning
confidence: 99%
“…First, we studied surface integrity and formation of metamorphic layer in high-speed milling 7055 aluminum alloy; 9 and then, we studied surface integrity and fatigue behavior in shot-peening for high-speed milled 7055 aluminum alloy; 19 now, we studied surface Integrity and fatigue analysis of shot-peening for 7055 aluminum alloy under different high-speed milling conditions. Shot peening process can reconstruct the microstructure and the hardened layer state of components.…”
Section: Discussionmentioning
confidence: 99%
“…Novovic et al 8 have carried out the system summary analysis, which is based on the previous research on fatigue life, and it was found that the change of the fatigue life of the parts is the combined effect of surface roughness, micro-hardness, residual stress, temperature, and other inclusions; if the correct operating parameters are employed, high-speed milling can provide enhanced fatigue performance. In order to get the optimum milling parameters of highspeed milling 7055 aluminum alloy, Yao et al 9 conducted the orthogonal experiment and finite element (FE) simulation to research the effect of milling parameters on surface integrity; the results show that when milling speed, feed per tooth, milling depth, and milling width are 1100 m/min, 0.02 mm/z, 0.7 mm, and 6 mm, respectively, good surface quality is obtained and the magnitude of surface metamorphic layer will be larger.…”
Section: Introductionmentioning
confidence: 99%